1977
DOI: 10.1002/oms.1210120903
|View full text |Cite
|
Sign up to set email alerts
|

Collisional activation of ions formed by [Li]+ ion attachment

Abstract: Since no unimolecular fragmentation is observed with [M+Li]+ ions under normal operating conditions the collisional activation method was used to study the fragmentation behaviour of these ions. it was found that the liberation of the The ionization of organic molecules by alkali ion attachment leads to quasimolecular ions which are very stable with respect to monomolecular decomposition^.'-^ Methods by which an alkali ion attachment can be achieved are of particular interest in organic mass spectrometry for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…LiNO 2 loss has been reported earlier in the CID spectra of lithiated benzenes. 9 The elimination of LiNO 2 is favoured only in compounds where R 3 is not equal to H. It is further favoured when the aryl group contains an NMe 2 group at the p-position. Elimination of HNO 2 occurs from [M + Li] + ions when R 3 is a cycloolefin group.…”
Section: Resultsmentioning
confidence: 99%
“…LiNO 2 loss has been reported earlier in the CID spectra of lithiated benzenes. 9 The elimination of LiNO 2 is favoured only in compounds where R 3 is not equal to H. It is further favoured when the aryl group contains an NMe 2 group at the p-position. Elimination of HNO 2 occurs from [M + Li] + ions when R 3 is a cycloolefin group.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Lee et al reported the highly selective cleavage of sodium-associated peptides from Asp residues; the sequential loss of amino acids from the C-terminus under low-energy CID were also observed when the peptide lacked acidic residues [32]. Rollgen et al first reported that the sodium ion interacts selectively with the polar functional groups of the peptides, initiating the backbone cleavage through a "charge remote" mechanism resulting in significant differences of the product ions from those formed by protonated peptides [38]. Various fragmentation mechanisms of the sodium-associated peptides have been proposed Table 2.…”
Section: ½ þmentioning
confidence: 99%
“…The presence of a fixed positive charge or a sodium ion in the peptide promoted this selective reaction [31][32][33]. Various mechanisms had been proposed to explain the formation of product ions formed via CID of [M+Na] + of peptides [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. For example, a sodium ion associated with the C-terminal carboxylic group has been proposed to initiate a rearrangement reaction of hydroxyl group leading to sequential loss of the C-terminal amino acid during multiple stages of MS/MS process [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The new ion source is of particular interest for producing high (M +alkali) + ion currents with unpolar or weakly polar molecules in order to study the decomposition behaviour of these ions following collisional activation [6,7]. In addition the mechanism of ion formation represents an attractive new field of research.…”
Section: Ionization Of Unpolar Molecules By Alkali Ion Attachment On mentioning
confidence: 99%